Analysis of Physico-Chemical Properties and Antioxidant Activity of Virgin Coconut Oil (VCO) Using Ordinary Tall Coconut Cultivars of North Halmahera (Agrikan Jurnal Agribisnis Perikanan, 2022)
Virgin coconut oil (VCO) contains medium chain fatty acids of which 45-50% lauric acid. Lauric acid has been proven to become a strong anti-inflammatory and anti-microbial agent. The objective of this study was to analyze of physico-chemical properties and antioxidant activity of VCO using Ordinary Tall Coconut Cultivars of North Halmahera with fermentation process. The results showed lauric acid (C12) is fatty acid (FA) in VCO were found containing predominantly 47.07%, while the total phenol content is about 11.23 mg GAE/ 100 g oil and antioxidant activity was determined using DPPH is 9.76 %. Especially for free fatty acid (FFA) content is range from 0.23%, iodine value is about 7.75%, the saponification value is about 256.39 (mg KOH/g), and moisture content ranges from 0.32%. The color is clear (colorless) and it is real aromatic coconut (VCO). Collectively, all results obtained in this study were found comparable with the Standard APCC except for linoleic acid, which has a slightly lower value compared to the standard value.
Keywords: VCO; fatty acid content; antioxidants; fermentation